The pretender. The complete fourth season [videorecording (DVD)] - Weiss, Michael T.; Parker, Andrea, 1969-; Bauchau, Patrick (20th Century Fox Home Entertainment, 2006)
Jarod is a pretender. He is a very intelligent person who has the ability to slide into somebody else's personality. For that purpose, he was taken from his family as a child in order to work for a secret agency called The Centre. After Jarod escapes The Centre, he has new missions in life - to help people in need with his gift, and to find out what really happened to his allegedly dead parents. Only, Miss Parker and her team are out to get him.